Placebo and Nocebo Effects in Patients With Takotsubo Cardiomyopathy and Heart-Healthy Controls - Olliges, Elisabeth; Schneider, Simon; Schmidt, Georg; Sinnecker, Daniel; Müller, Alexander; Burgdorf, Christof; Braun, Siegmund; Holdenrieder, Stefan; Ebell, Hansjörg; Ladwig, Karl-Heinz; Meissner, Karin; Ronel, Joram (Frontiers in Psychiatry, 2019)
The etiology of Takotsubo Cardiomyopathy (TTC) – a rare, reversible, and acquired form of car-diac diseases – is not yet fully explained. An exaggerated activation of the sympathetic-nervous-system (SNS) following stressful psychosocial life events is discussed to be of key importance. In this experimental study, we tested whether TTC patients, compared to heart-healthy controls, respond more strongly to supporting placebo interventions and stressful nocebo interventions tar-geting cardiac function. In a single experimental session, 20 female TTC patients and 20 age matched (mean age 61.5 years, ± 12.89) catheter-confirmed heart-healthy women were examined. Saline solution was ad-ministered three times i.v. to all participants, with the verbal suggestion they receive an inert sub-stance with no effects on the heart (neutral condition), a drug that would support cardiac func-tions (positive condition), and a drug that would burden the heart (negative condition). Systolic and diastolic blood pressure (DBP/SBP), heart rate (HR), endocrine markers cortisol (µg/dl) and copeptin (pmol/l) and subjective stress ratings (SUD) were assessed to examine alterations of the SNS and the hypothalamic–pituitary–adrenal axis (HPA). Before and after each intervention SUD was rated. One pre and three post serum cortisol and copeptin samples were assessed, and a long-term electrocardiogram as well as non-invasive, continuous blood pressure was recorded. The study design elucidated a significant increase of SUD levels as a response to the nocebo in-tervention, while perceived stress remained unaffected during the preceding neutral and positive interventions. Increasing SUD levels were accompanied by higher SBP and an anticipatory in-crease of HR shortly prior to the nocebo intervention. SBP increased also as a response to positive verbal suggestions (Bonferroni-corrected p-values > .05). Alterations of cortisol and copeptin due to the interventions and significant placebo effects failed to appear. Interestingly no differences between TCC patients and controls could be found. These findings do not support the assumption of an exaggerated activation of the SNS as a dis-criminatory factor for TTC. Since especially the nocebo intervention revealed negative subjective and objective effects, our results underscore the urgent need to consider carefully the impact of verbal suggestions in the interaction with cardiac patients in daily clinical routine.